2000
DOI: 10.1046/j.1365-2702.2000.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain and nutrition as experienced by patients with hip fracture

Abstract: The purpose of this study was to investigate patients' experiences of care in connection with hip fracture. The care process was examined through non-participant observation, informal field interviews and healthcare records. The findings showed that many factors in the healthcare services directly or indirectly influence patients' perceptions of the quality of care. Some of these factors may depend upon a varying knowledge and empathy, while others are due to a lack of agreed protocols/procedures. Patients' ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
35
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
5
35
0
1
Order By: Relevance
“…Management of acute postoperative pain is a central issue in elderly patients with hip fracture. However, pain is often under-assessed and patients need to be relieved from pain to become mobile (Hallström et al, 2000). It is also important to assess pain and give pain relief to avoid PU (Hommel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Management of acute postoperative pain is a central issue in elderly patients with hip fracture. However, pain is often under-assessed and patients need to be relieved from pain to become mobile (Hallström et al, 2000). It is also important to assess pain and give pain relief to avoid PU (Hommel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28]40,42 Although the literature is replete with prescriptive models of how patients should make decisions, 10,21,22,24,31,34,43 no studies were identified that specifically examined patient strategies for making decisions about managing their pain in actual practice. Instead, patients' perspectives on pain management have mainly been addressed with descriptions of their experience, 1,[7][8][9]16,19 their perceived satisfaction with care activities, 20,23,37 and their attitudes concerning the pain experience. 5,39 Common postoperative experiences relating to pain management include patients' refusal to accept analgesia, 8 patients behaving passively about asking for analgesia, and patients believing they have to tolerate pain.…”
mentioning
confidence: 99%
“…5,39 Common postoperative experiences relating to pain management include patients' refusal to accept analgesia, 8 patients behaving passively about asking for analgesia, and patients believing they have to tolerate pain. 8,16 Patients may not disclose pain to clinicians because they are perceived to be too busy. 5,9,16,41 There is also a tendency for patients not to actively communicate with clinicians following operations about how they want their pain to be treated.…”
mentioning
confidence: 99%
See 2 more Smart Citations